Integrating Digital Skills into Vocational Education for Automation-Era Workforce Readiness - Lod Sulivyo; Umi Rusilowati; Abdullah Arif Kamal; Meriyana Sunengsih (Jurnal MENTARI: Manajemen, Pendidikan dan Teknologi Informasi, 2026)
This study examines the integration of digital skill competencies into vocational education curricula as a strategic response to rapid technological development and increasing automation across industrial sectors. Vocational institutions are expected to equip learners with the digital capabilities necessary to remain competitive in a shifting labor market. However, many existing curricula still lack structured and industry-aligned digital components, creating a gap between educational outputs and workforce demands. To address this issue, the research employs a mixed-methods approach combining quantitative surveys and qualitative interviews to evaluate the relevance and effectiveness of digital skill integration. A total of 120 respondents, consisting of vocational students, teachers, and industry partners, participated in a structured questionnaire designed to assess current digital competencies, curriculum adequacy, and perceived readiness for automated work environments. Additionally, in-depth interviews were conducted with selected educators and industry stakeholders to gain deeper insights into curriculum reform needs and emerging digital skill requirements. The findings indicate that while vocational institutions have initiated the adoption of digital learning tools, the integration of advanced competencies such as data literacy, digital collaboration, and automation-related technical skills remains limited and inconsistent. Respondents highlighted the need for curriculum redesign that incorporates practical, industry-responsive digital modules supported by continuous professional development for teachers. This study contributes a framework for enhancing digital competency integration within vocational education, ultimately aiming to strengthen workforce readiness and ensure graduates can effectively adapt to the evolving demands of the automation era.